2012
DOI: 10.17221/195/2012-pse
|View full text |Cite
|
Sign up to set email alerts
|

Ground cover and leaf area index relationship in a grass, legume and crucifer crop

Abstract: Canopy characterization is essential for describing the interaction of a crop with its environment. The goal of this work was to determine the relationship between leaf area index (LAI) and ground cover (GC) in a grass, a legume and a crucifer crop, and to assess the feasibility of using these relationships as well as LAI-2000 readings to estimate LAI. Twelve plots were sown with either barley (Hordeum vulgare L.), vetch (Vicia sativa L.), or rape (Brassica napus L.). On 10 sampling dates the LAI (both direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…In Skaryszewski Park the correlation coefficient between LAI and leaves coverage was equal to 0.94 and, between LAI and sward height it was equal to 0.95. According to Lambert et al (1999) and Ramirez-Garcia et al (2012) LAI value for vascular plant species could be affected by: number of tillers, number of leaves per tiller and average area of leaves.…”
Section: Resultsmentioning
confidence: 99%
“…In Skaryszewski Park the correlation coefficient between LAI and leaves coverage was equal to 0.94 and, between LAI and sward height it was equal to 0.95. According to Lambert et al (1999) and Ramirez-Garcia et al (2012) LAI value for vascular plant species could be affected by: number of tillers, number of leaves per tiller and average area of leaves.…”
Section: Resultsmentioning
confidence: 99%
“…When the soil is covered by some dead residue, the transpiration is equal to 0 and the evaporation is calculated for the bare soil but multiplied by the fraction of soil that is not covered. The soil cover fraction was obtained from the LAI and corrected following 25 Ramirez-Garcia et al (2012).…”
Section: Wave Modelmentioning
confidence: 99%
“…Concerning the herbaceous vegetation, Gosa, A.G. et al (2007) reported LAI between 0.7 and 4.5, while Ramiréz- García, J. et al (2012) summarized LAI of meadows between 2 and 3. For higher vegetation, LAI between 1.5 and 5.7 is reported for shrubs and between 4.5 and 10.6 for forests (Gosa, A.G. et al 2007).…”
Section: Introductionmentioning
confidence: 99%